A community hospital's approach towards same-day discharge after minimally invasive hysterectomies during the COVID-19 pandemic. Issue 28 (1st October 2022) - Chien, Christine; Cheng, Georgina
Abstract : 347 Objectives: We performed a quality improvement project to evaluate the trends and safety of same-day discharge after minimally invasive hysterectomies at a community hospital during the COVID-19 pandemic and beyond. Background: The COVID-19 pandemic created an unprecedented demand on hospital resources as patients rapidly filled hospital beds. From March 16 to May 11, 2020, the Illinois Department of Public Health advised the cancellation of elective surgeries to reduce the burden on the health care system. Same-day discharge after hysterectomy has been trending since before the pandemic, but most research touting its safety describes its success among a select group of patients, generally young with few comorbidities, undergoing simple surgeries. We investigate how Carle Foundation Hospital (CFH) employed same-day discharge after hysterectomies during the pandemic. Methods: As a quality improvement project, we performed a retrospective review of patients who underwent hysterectomies at CFH before the start of the pandemic (November 2019 to February 2020) and afterwards (March to November 2020). Minimally invasive hysterectomies performed using either laparoscopic or robotic approaches were considered. Both benign and oncological cases were included. Same-day discharge was defined as no overnight stay after surgery. Patients discharged day of surgery were compared to those with overnight stays. Patient risk factors analyzed included age, race, body mass index (BMI), ASA score, malignancy, length of operation, estimated blood loss, zip code, and post-operative pain scores. Our primary outcomes were complications, ED visits, and readmissions within 30 days of surgery. Multivariate logistic regression was used to identify factors associated with negative outcomes. Results: From November 2019 to November 2020, 353 patients received minimally invasive hysterectomies at CFH. 294 (72.8%) hysterectomies were performed robotically. Rates of same-day discharge remained at 51% before and during the COVID-19 pandemic. Robotic hysterectomies were more likely to be discharged same day than laparoscopic (54% vs. 36%). Longer procedure time and living further from the hospital were significant predictors of overnight admissions, whereas age, BMI, ASA score, and post-operative pain were not. The rates of complications, ED visits, and readmissions did not significantly increase during this timeframe, nor was same-day discharge associated with a greater risk of negative outcomes overall. Conclusions: Our findings suggest that same-day discharge is safe after minimally invasive hysterectomies for patients who are average risk or below. Furthermore, the implementation of a carefully designed intervention at CFH may be able to safely raise rates of same-day discharge and conserve hospital resources.